In vitro screening for anti-microbial activity of chitosans and chitooligosaccharides, aiming at potential uses in functional textiles - Fernandes, João C; Tavaria, Freni K; Fonseca, Susana C.; Ramos, Óscar S; Pintado, Manuela E.; Malcata, F Xavier (Journal of microbiology and biotechnology, 2010)
Antimicrobial finishing of textiles has been found to be an economical way to prevent (or treat) skin disorders. Hence, this research effort was aimed at elucidating the relationship between molecular weight (MW) of chitosan and its antimicrobial activity upon six dermal reference microorganisms, as well as the influence of the interactions with cotton fabrics on said activity. Using 3 chitosans with different MW, as well as two chitooligosaccharide (COS) mixtures, a relevant antimicrobial effect was observed by 24 h for the six microorganisms tested; it was apparent that the antimicrobial effect is strongly dependent on the type of target microorganism and on the MW of chitosan being higher for lower MW in the case of E. coli, K. pneumoniae and P. aeruginosa, and the reverse in the case of both Gram-positive bacteria. Furthermore, a strong anti-fungal effect was detectable upon C. albicans, resembling the action over Gram-positive bacteria. Interactions with cotton fabric resulted in a loss of COS activity when compared with cultured media, relative to the effect over Gram-negative bacteria. However, no significant differences for the efficacy of all the 5 compounds were observed by 4 h. The three chitosans possessed a higher antimicrobial activity when impregnated onto the fabric, and presented a similar effect on both Gram-positive bacteria and yeast, in either matrix. Pseudomonas aeruginosa showed to be the most resistant microorganism to all five compounds.